Efficacy of soy-lecithin for replacing egg yolk in tris extender on quality of frozen buck semen - KALITA, MANOJ KUMAR; SINHA, SUDIP; DEKA, BHARAT CHANDRA; BISWAS, RANJAN KUMAR; BARKALITA, LUITMANI; BORAH, RUMI SAIKIA (The Indian Journal of Animal Sciences, 2019)
The present study undetaken to find the efficacy of incorporating soy-lecithin in tris extender for replacing egg yolk, a widely used animal component. Pooled ejaculates (40), 10 from each of four bucks maintained at Goat Research Station, Burnihat were used for freezing in tris extender containing 1% and 1.5% soy-lecithin and 20% egg yolk by adopting split sample technique following conventional method. The post thaw sperm motility in 1.5% soy-lecithin-tris extender (60.20Â±0.45%) was comparable with that of 20% egg yolk-tris (61.20Â±0.45%), the difference being non-significant. However, the post thaw values for live sperm, intact acrosome and hypo-osmotic swollen sperm were significantly lower in 1.5% soy-lecithin-tris as compared to that in 20% egg yolk-tris. The post thaw values were significantly higher for 1.5% than that for 1% soy-lecithin for all the parameters studied. It could be concluded that 1.5% soy-lecithin-tris extender has similar efficacy with that of 20% egg yolk-tris extender in respect of post thaw sperm motility; however, significantly lower post thaw values for remaining sperm qualities obtained with soy-lecithin in tris-based extender necessitate further trials comprising higher number of ejaculates from more bucks to find a suitable level of soy-lecithin for replacing egg yolk in tris extender for freezing of goat semen.